Lo que no habíamos dicho Documental autobiográfico sobre la relación madre e hija - Romero Capcha, Valeria Enith (2023)
What we had not said is a reflexive autobiographical documentary about the motherdaughter relationship, in which the director immerses herself in her memory to understand and rebuild her identity, based on the story she shares with her mother. Through archive material and an intimate dialogue between the two, topics that intrinsically link the role assigned to women in the peruvian society are touched, such as marriage, motherhood, separation from a partner and crisis personal growth. The purpose of the project is related to promoting reflections and collective awareness on the role of women's identity and representing the memory of the impact of a mother on the identity of a daughter, considering the current social context.